The Osmotic Potential of Polyethylene Glycol 6000 - Michel, Burlyn E. (1973)
Osmotic potential (ψ(s)) of aqueous solutions of polyethylene glycol 6000 (PEG-6000) was curvilinearly related to concentration. At given concentrations, ψ(s) increased linearly with temperature. The effects of concentration and temperature on ψ(s) of PEG-6000 solutions differ from those for most salts and sugars and apparently are related to structural changes in the PEG polymer. Measurements of ψ(s) with thermocouple psychrometers are more negative than those with a vapor pressure osmometer, with the psychrometer probably giving the more nearly correct ψ(s) for bulk solutions. An empirical equation permits calculation of ψ(s) from known concentrations of PEG-6000 over a temperature range of 15 to 35 C. Viscometery and gravimetric analysis are convenient methods by which the concentrations of PEG-6000 solutions may be measured.